#TITLE_ALTERNATIVE# - Susanto Hariyadi (NIM 350 02 006), Eri
Abstract: The condition of bonding between asphalt pavement layer can influence the behaviour of pavement structure in supporting vehicle loading. In strong bonding condition, the adjacent pavement layers will act together to support pavement loading and the other way in weak bonding condition the layers will act independently with the result that stress in every layer of pavement become higher and will decrease pavement life consequently. The objective of this research is to develop the method to quantifying bonding condition between asphalt pavement layers using the certain parameters. The scope of this research is investigating bonding condition between asphalt pavement layers using theoretical simulation and laboratory approach. The comprehensive reviews of previous researchs are applied as a basis for developing method to evaluate bonding condition between asphalt pavmenet layers. In simulation approach, finite elemen method using SAP2000 computer program was carried out to analyze theoretical pavement structure and exploring bonding condition between wearing course and binder course. M-ESH Generation computer program was developed as SAP2000 user interface to make easy for creating finite element model for layered pavement structure. The structure analysis results which were resulted by this program were compared with CIRCLY 5 program to validate the sructural reponses. The results show that the rstructural responses have a good agreement between SAP2000 and CIRCLY5 which especially designed for pavement structural analysis. In modeling pavement structure using finite element method, axisymetric model can be used for their structural analysis. Applying thin layer in representing the interface with a bonding condition was a good application. This modulus of thin layer can be used as parameter for bonding condition between asphalt pavement layers. In full bonding condition, thin layer modulus has the same value with modulus of adjacent layers. In partial bonding condition, the decreasing of thin layer modulus will lead bonding condition approaching the smooth condition and increasing thin layer modulus will lead bonding condition approaching rough condition. This parameter of thin layer modulus can be used for designing pavement layer thickness involving bonding condition. If the bonding condition become weak then the required thickness of pavement layer become higher. This simulation approach also show that the new factor can be introduced for factor which can cause early pavement damage in related to the design of pavement thickness is assumption of bonding condition.